PENYULUHAN TENTANG UPAYA MENGHINDARI STROKE PADA IBU RUMAH TANGGA BERUSIA 30 TAHUN KE ATAS - Moh. Ubaidillah Faqih; Kusno Ferianto (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2023)
Stroke is a disease that is a problem in the world, 85% of the world's population is at risk of stroke. Stroke is a chronic disease that has a dangerous impact. by impaired blood circulation to the brain due to arterial blood vessels due to deposits blood in the veins, rupture of the veins blood or abnormalities in the condition of the blood itself resulting in a lack of oxygen supply and nutrients to the brain which causes brain tissue damage. lack of knowledge of patients, families and the general public about stroke, its signs, symptoms, and good lifestyle for stroke sufferers such as eating instant food. community service about stroke if properly explained can be encouraging stroke sufferers to immediately seek treatment so that the impact of death and disability can be overcome or minimized.